RANCANG BANGUN ALAT PENGERING BAJU MENGGUNAKAN UDARA PANAS - Kadriadi, Kadriadi; Wirakusuma, Kadex Widhy; Pratama, Angga Bahri; Ariksa, Jeri; Yandi, Welly (Machine : Jurnal Teknik Mesin, 2023)
Drying is a process of transferring heat and water vapor simultaneously which requires heat energy to evaporate the water content. This heat energy can usually be obtained from sunlight. However, during the rainy season, this condition inhibits the drying process that utilizes sunlight, so the drying process takes a long time. Therefore we need a tool that can dry clothes without depending on the heat source from the sun's rays. The clothes dryer is a tool used to dry clothes with artificial heat energy, one of the artificial heat producers is a heating element or what is often called a heater. The artificial heating element used in this research is Electric Heater. This Electric Heater is equipped with a fan that can produce an indoor temperature of up to ± 52.3º C so that the heat generated by the Electric Heater can convert the water contained in the clothes into water vapor which will then be released into the environment with the help of a fan. Based on the results of calculations and testing, the ability of this tool is able to evaporate an average mass of water of 535.8 grams/hour and this machine reaches its optimum point for the number of drying clothes that can be dried as many as 6 clothes.